Odpowiedź :
Odpowiedź:
a) -2(5x + 2) = 3 -9x
-10x - 4 = 3 -9x
-10x + 9x = 3+ 4
-x = 7 //: (-1)
x = -7
b) y/2 + 1/3 = 7/6 //*2
y + 2/3 = 7/3
y = 7/3 - 2/3
y = 5/3
c) 0,2x + 0,3 = 1,3
0,2x = 1,3 - 0,3
0,2x = 1 //:0,2
x=5
[tex]Zadanie\\\\a)\\\\-2(5x+2)=3-9x\\\\-10x-4=3-9x\ \ \mid+4\\\\-10x=7-9x\ \ \mid+9x\\\\ -x=7\ \ \mid\cdot(-1)\\\\x=-7\\\\b)\\\\\frac{y}{2}+\frac{1}{3}=\frac{7}{6}\ \ \mid\cdot6 \\\\3y+2=7\ \ \mid-2\\\\3y=5\ \ \mid:3\\\\y=\frac{5}{3}\\\\y=1\frac{2}{3}\\\\c)\\\\0,2x+ 0,3=1,3\ \ \mid\cdot10\\\\2x+3=13\ \ \mid-3\\\\2x=10\ \ \mid:2\\\\x=5[/tex]